The English Influence on Japanese, Indonesian and Malang Slang Words: a Study of Wakamono Kotoba, Bahasa Gaul, and Slang Malang - Suraida Nurul Oktavia; Vera Yulianti (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2021)
In the characteristics of the morphological formation of Japanese slang words (Wakamono Kotoba), Indonesian slang words (Bahasa Gaul), and Malang slang words (Slang Malang), there is a phenomenon of English influence. The purpose of this study is to examine the morphological characteristics of the English influence on Japanese slang words (Wakamono Kotoba), Indonesian slang words (Bahasa Gaul), and Malang slang words (Slang Malang). The data was collected from Twitter accounts which the users are native Japanese language, native Indonesian language, and native Malang language. The analysis was based on the classification of word-formation categories Akihiko Yonekawa (Yonekawa, 1998). The result of the study shows that the English influence on Japanese slang words is in the category of English borrowing and the combination of Japanese and English. Meanwhile, the English influence on Indonesian slang words and Malang slang words is only in the form of English borrowing.